Soviet Strategy and NATO's Northern Flank. - Sullivan,William K (1978)
For historical, political, and military reasons, the Soviet Union has coveted the Nordic region, encompassing Norway, Sweden, and Denmark and the surrounding waters. The Soviet's overriding strategic objectives in the Nordic region are to protect its northern flank and secure the sea lines of communication to the North Atlantic from the Murmansk area through the Barents and North Seas and from the Leningrad area through the Baltic and North Seas. In pursuit of the above objectives, the Soviets are expanding their area of influence farther westward from the naval bases of the Baltic and Barents Seas to the forward defense line of Western naval strategy in the North Atlantic, the strategic Greenland-Iceland-United Kingdom gap. This expansion of Soviet naval jurisdiction, by flanking movements through the Barents, Norwegian, Baltic, and North Seas, may eventually be intended to isolate the Nordic region from Western influence and eradicate NATO's Northern Flank. The NATO Alliance must recognize that the resolution of the security problems along the Northern Flank may essentially be a naval issue.